THE EFFECT OF GIVING ALOE VERA GEL ON RATS WITH BACTERIA-INDUCED PERIODONTITIS - Abdurrohman, Muhamat Muhtar S; Putranto, Rama; Suhartono, Budi; Fa'adiyah, Dhiya almanda (Odonto : Dental Journal, 2021)
ABSTRACTBackground: Aloe vera (AV) contains a variety of characteristic antibiotic and anti-inflammatory components that have potential advantages for periodontal disease therapy. Diagnostic and prognostic markers of periodontal disease through the activity of alkaline phosphatase (ALP) in gingival crevicular fluid. This study was conducted to evaluate the effect of giving AV gel on alkaline phosphatase levels in rats with bacteria-induced periodontitisMethod: Thirty-six male Sprague dawley were healthy and active, weighing 170-200 grams, aged 2 months were distinguished into two groups: the control group of periodontitis given therapy Gel Metronidazole plus 25% and AV gel 99.03% as a treatment group. Aloe vera gel is administered topically in gingival sulcus at a dose of 300 mg/kg of rat weight. Samples were taken from gingival sulcus liquid on days 1, 2 and 3 using periopaper paper. Alkaline phosphatase levels are measured using a UV/Vis Spectrophotometer with a wavelength of 405 nm. Variant analysis is used to compare ALP levels in different groupsResult: There was significant difference in alkaline phosphatase levels between the control group and the treatment group (p>0.05). In Sprague dawley rats with periodontitis, there was a significant decrease in ALP levels on days 1, 2 and 3 given Metronidazole gel plus 25% therapy and AV gel 99.03%. But the treatment group showed lower ALP levels than the control groupConclusion: This study revealed that the use of AV gel locally has an effect and can be as an adjunct therapy for periodontitis